2021
DOI: 10.1186/s12911-021-01715-3
|View full text |Cite
|
Sign up to set email alerts
|

dfgcompare: a library to support process variant analysis through Markov models

Abstract: Background Data-driven process analysis is an important area that relies on software support. Process variant analysis is a sort of analysis technique in which analysts compare executed process variants, a.k.a. process cohorts. This comparison can help to identify insights for improving processes. There are a few software supports to enable process cohort comparison based on the frequencies of process activities and performance metrics. These metrics are effective in cohort analysis, but they c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Hou et al confirmed that nurses using an electronic handover system can improve their communication efficiency [58]. Jalali et al discovered that information systems involving drug interactions can support physicians in making decisions more efficiently [59]. Literature evidence on the impact of satisfaction suggests that employees who are satisfied with a system are more likely to be more productive, especially if the use of such a system is mandated [60][61][62].…”
Section: Influence Of Use Intention and Satisfaction On Net Benefitsmentioning
confidence: 99%
“…Hou et al confirmed that nurses using an electronic handover system can improve their communication efficiency [58]. Jalali et al discovered that information systems involving drug interactions can support physicians in making decisions more efficiently [59]. Literature evidence on the impact of satisfaction suggests that employees who are satisfied with a system are more likely to be more productive, especially if the use of such a system is mandated [60][61][62].…”
Section: Influence Of Use Intention and Satisfaction On Net Benefitsmentioning
confidence: 99%
“…This graph is used to calculate a similarity matrix that enables the clustering of the case notions based on a threshold. Markov clustering is selected as it is widely applied in practice for different purposes, e.g., identifying protein-protein interaction networks [14], traffic state clustering [16], document clustering [11], and comparing similarities between different process variants [12]. To answer the second research question, a threshold tuning algorithm is defined to identify sets of different clusters that can be discovered based on all possible thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…Although DFGs can be misleading due to lack of support for concurrency [22], they can be helpful as an intermediate model to discover more advanced models as done by, e.g., Split Miner [3], Heuristics Miner [25] and Fodina [24]. DFGs are also used in variant analysis where different models of a business process representing different variations can be compared to each other [12], [17], [18].…”
Section: Introductionmentioning
confidence: 99%